PENGARUH PRIOR EXPERIENCE DAN PRODUCT KNOWLEDGE TERHADAP SWITCHING BEHAVIOUR DALAM PEMBELIAN HANDPHONE DENGAN MEDIASI SATISFACTION (Students' Journal of Economic and Management, 2013)
This study aimed to analyze the effect of Prior experience and Product Knowledge on Switching Behavior in the purchase of a mobile phone with mediation Satisfaction. Brand switching behavior arising from the presence of variety seeking behavior need attention from marketers. This behavior not only in products with a low level of involvement, but also occur in products with a high level of involvement (high involvement).Samples taken are consumers handpone owner PIP Semarang in residential areas that have never switched brands of mobile phones within the last 3 years, amounting to 100 people repsonden.Based on the analysis results obtained using the t test ,t test variable value conclusion Prior experience at .927 with .357 sig sig t test (>) 0.05 so it can be concluded that the variable Prior experience positive but not significant effect on Satisfaction. T test value of 20 967 Variable Product knowledge with .000 sig sig t test (<) .005 so it can be concluded that the variable Product knowledge and significant positive effect on satisfaction. The value of the variable t test of 0.007 Prior experience with .994 sig sig t test (>) 0.05 so it can be concluded that the variable Prior experience positive and significant effect on switching behavior. Value Product knowledge variable t test for 3910 with .000 sig sig t test (<) 0.05 so it can be concluded that the Product knowledge and significant positive effect on switching behavior. Satisfaction variable t test values ​​for 3779 with .000 sig sig (<) 0.05 so it can be concluded that the variable Satisfaction has positive and significant impact on switching behavior. Keywords: Prior Experience, Product Knowledge, Satisfaction and Switching Behaviour